Development of a Computer Programme for the Static Analysis of Jacket Offshore Structures Subjected to Wave and Current Loading - Bahrom, Samsul Imran (2006)
Jacket structures are the most commonly used type of offshore structure in the world for oil and gas development. This thesis is concerned with the static response of a typical jacket structure subjected to wave and current forces using an innovative physical model of the soil-foundation-structure system. The motivation is to demonstrate the applicability of using a coupled finite-infinite element formulation to represent the far field media of the soil for offshore structural analysis. Techniques to represent the environmental load and the physical model for static analyses of fixed slender offshore structures are reviewed. Based on the techniques suitable for engineering purposes, a computer code for calculating wave and current forces is written and its implementation into an existing multi-element finite element programme is outlined. For comparison purposes, the developed programmes are checked against a commercial software package through several model tests.The range and versatility of the coupled programme is demonstrated through structural analyses of a typical jacket structure. The effects of different wave parameters, load combinations and a comparison of structural response assuming i) fixity at the base and ii) flexibility of elastic foundations are studied in detail with respect to displacements, axial forces and bending moments. The advantages and potential of using a coupled finite-infinite formulation for physical representation of the soil for offshore structural analysis are also pointed out and discussed.